Does the COVID-19 Pandemic Affect Morbidity and Mortality Rates of Emergency General Surgery? A Retrospective Study from a Single-Center Tertiary Greek Hospital - Eleni Karlafti (MDPI AG, 2021)
Background and Objectives: The outbreak of the COVID-19 pandemic had a major impact on all aspects of health care. Few up-to-date studies have actually assessed the impact of COVID-19 on emergency surgeries. The aim of this study was to provide an overview of the impact of the pandemic relating to the emergency surgery performed, as well as morbidity and mortality rates during the first year of the pandemic (March 2020–February 2021) and during the control period. In this period, the first propaedeutic surgery department and the third surgery department of the University General Hospital of Thessaloniki “AHEPA” in Greece provided continuous emergency general surgery services. Material and Methods: The study is in a retrospective cohort and included patients who were admitted to the Emergency Department and underwent emergency general surgery during the control period (n = 456), March 2019–February 2020 and during the first year of the pandemic (n = 223), March 2020–February 2021. Gender, age, type of surgical operation (morbidity), ICU need, the patient’s outcome, and days of hospitalization were compared. Results: A total of 679 emergency surgeries were included. Statistically significant differences emerged between the two time periods in the total number of emergency surgeries performed (p < 0.001). The most common type of surgery in the control period was associated with soft tissue infection while, during the pandemic period, the most common type of surgery was associated with the hepatobiliary system. In addition, the mortality rates nearly doubled during the pandemic period (2.2% vs. 4%). Finally, the mean age of our sample was 50.6 ± 17.5 and the majority of the participants in both time periods were males. Conclusions: The COVID-19 pandemic changed significantly the total number of emergency general surgeries performed. Mortality rates doubled and morbidity rates were affected between the control and pandemic periods. Finally, age, gender, length of hospitalization, intensive care unit hospitalization, and laparoscopy use in patients undergoing emergency surgery during the pandemic were stable.